Which Classes of Antibiotics Are Associated with the Acquisition of Carbapenemase-Producing Enterobacterales? - Lisa Sadou; Benoît Pilmis; Rasha Eid; Pierre Moenne Locoz; Sophie Lefèvre; Françoise Jauréguy; Vanessa Rathouin; Jean-Ralph Zahar; Laura Foucault-Fruchard (Life, 2025)
Background: Enterobacterales are among the most frequent causes of healthcare-associated infections and are increasingly affected by antimicrobial resistance. Antibiotic use disrupts the gut microbiota, facilitating colonization by multidrug-resistant organisms, including carbapenemase-producing Enterobacterales (CPE). While animal studies have suggested that certain antibiotic classes may increase the risk of CPE acquisition, clinical data identifying which classes are most implicated remain limited. Methods: We conducted a single-center, retrospective case-control study (2021–2024) comparing antibiotic prescriptions in patients who acquired CPE with those in controls hospitalized in the same unit and during the same risk period but who did not acquire CPE. The objective of this study was to identify which antibiotic classes or pharmacological properties are associated with the acquisition of carbapenemase-producing Enterobacterales (CPE) in hospitalized patients. Results: During the study period, 35 cases and 70 controls were included. Most cases acquired NDM-type metalloenzymes. Before the risk period, 55 patients had received antibiotic therapy. Univariate analysis identified an association between CPE acquisition and the prescription of fluoroquinolones and antibiotics excreted in bile. During the risk period, only metronidazole prescription was significantly associated with CPE acquisition. Our study has several limitations, including the small sample size, the single-center retrospective design, and the lack of molecular typing (e.g., WGS) to confirm potential clonal transmission. Conclusions: In this preliminary study, metronidazole use was associated with an increased risk of CPE acquisition during risk periods. However, these results should be interpreted cautiously and need to be confirmed in larger, multicenter studies. The high exposure of patients to multiple antibiotic classes highlights the importance of strict antibiotic stewardship policies in the current era of global CPE dissemination.